2010
DOI: 10.1590/s0101-20612010000200031
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antioxidante e teor de fenólicos totais em hortaliças orgânicas e convencionais

Abstract: O sistema de produção denominado atualmente de convencional baseia-se na utilização intensiva de insumos químicos (agrotóxicos), mecanização pesada e melhoramento genético voltado para a produtividade física. No entanto, esse padrão de produção visando exclusivamente à produtividade, vem sendo muito questionado, em função da divulgação de aspectos negativos, tais como esgotamento dos recursos naturais, degradação ambiental, exclusão social, elevação dos custos de produção, contaminação dos alimentos por agrotó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 20 publications
0
21
0
13
Order By: Relevance
“…Nevertheless some researchers found higher antioxidant activity values in organic compared to conventional crops (Aldrich et al, 2010;Arbos et al, 2010;Borguini et al, 2013). We expected that the highest antioxidant activity, among fruits, will be measured in raspberries.…”
Section: Analysis Of Variancementioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless some researchers found higher antioxidant activity values in organic compared to conventional crops (Aldrich et al, 2010;Arbos et al, 2010;Borguini et al, 2013). We expected that the highest antioxidant activity, among fruits, will be measured in raspberries.…”
Section: Analysis Of Variancementioning
confidence: 88%
“…Weibel et al (2000) showed that fruit quality of organic apples were either similar or slightly better than that of conventional ones. According to literature data, the organic crops presented higher antioxidant activity than conventional ones (Worthington, 2001;Wang et al, 2008;Aldrich et al, 2010;Arbos et al, 2010;Crinnion, 2010;Lairon, 2010;Borguini et al, 2013). This can be attributed to the fact that organic farming uses less phytopharmacheuticals and plant therefore develop several defense mechanisms (Koleva et al, 2002;Borguini et al, 2013).…”
Section: Descriptive Statisticmentioning
confidence: 99%
“…Nos estudos realizados por Machado (2012) com brócolis (Brassica oleracea var. Italica) e por Arbos et al (2010) com almeirão, alface, e rúcula também foram encontrados percentuais mais elevados de AA em hortaliças submetidas ao cultivo orgânico.…”
Section: Discussionunclassified
“…Além disso, relata-se que possíveis incidências de pragas e patógenos, no sistema de cultivo orgânico, podem provocar um aumento significativo no teor de compostos fenólicos pelas plantas, com o objetivo de aumentar suas próprias defesas naturais (ASAMI et al, 2003). Arbos et al (2010) Vale ressaltar que, resultados divergentes quanto ao efeito do tratamento térmico sobre o teor de fenólicos podem ser atribuídos à falta de padronização quanto à forma de cálculo da estabilidade e a correção para alterações de peso (CAMPOS et al, 2008).…”
Section: Discussionunclassified
“…The experimental results were expressed as the reduction of the free radical DPPH by 50%. The parameter EC 50 , which represents the inhibitory concentration necessary for this reduction, was used (QIAN; NIHORIMBERE, 2004;ARBOS et al, 2010 (CANSIAN et al, 2010). Table 3 presents some published results of EC 50 obtained using the DPPH method for some species of plants and different solvents used to extract essential …”
Section: Dpph Radical Scavenging Methodsmentioning
confidence: 99%